Using Clients' Artistic Expressions as Metaphor in Counselling: A Pilot Study - Ulak, Beverly J.; Cummings, Anne L. (Canadian Journal of Counselling and Psychotherapy, 2007)
Six clients were asked to draw pictorial representations of their problematic situations and then discuss them by identifying with the elements of their drawings as parts of themselves. Using The Experiencing Scale (Klein, Mathieu-Coughlan, & Kiesler, 1986), pre-art intervention dialogue and post-art intervention dialogue were assessed for level of experiencing. Level of experiencing increased as clients discussed their pictures, t = 12.6, p < .01 . Qualitative observations of client behaviour during this section of the counselling sessions also supported a change to a higher level of experiencing.